2014
DOI: 10.1016/j.jpeds.2014.05.050
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Obesity, Gestational Weight Gain, and Offspring Adiposity: The Exploring Perinatal Outcomes among Children Study

Abstract: Objective To determine if adequate versus excessive gestational weight gain (GWG) attenuated the association between maternal obesity and offspring outcomes. Study design Data from 313 mother-child pairs participating in the Exploring Perinatal Outcomes in Children (EPOCH) study were used to test this hypothesis. Maternal pre-pregnancy body mass index (BMI) and weight measures throughout pregnancy were abstracted from electronic medical records. GWG was categorized according to the 2009 Institute of Medicine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
82
0
11

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(99 citation statements)
references
References 29 publications
6
82
0
11
Order By: Relevance
“…This is conceivable because healthy pregnant women may compensate for much of the assumed increased energy needs by selecting less demanding physical activities (5). Recommending additional energy intake may therefore contribute to the increasing prevalence of excessive weight gain in pregnancy, a risk factor for gestational diabetes and offspring obesity (6)(7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is conceivable because healthy pregnant women may compensate for much of the assumed increased energy needs by selecting less demanding physical activities (5). Recommending additional energy intake may therefore contribute to the increasing prevalence of excessive weight gain in pregnancy, a risk factor for gestational diabetes and offspring obesity (6)(7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…Carbohydratecontaining foods can be assessed for nutritional quality according to various measures, including whole-grain content, added sugar, and high or low glycemic index (GI). 7 The GI [a ranking of carbohydrate foods by their glycemic potency (18)] and glycemic load (GL, the mathematical product of the GI and carbohydrate per serving) capture the postprandial glycemic response to a food (19). In a previous study in women with gestational diabetes mellitus, lower dietary GL was associated with improved dietary quality, whereas intake of grain and cereal products was 1 Supported by Illawarra Shoalhaven Local Health District, National Health and Medical Research Council, and the University of Sydney 2 Supplemental Table 1 is available from the "Supplemental data" link in the online posting of the article and from the same link in the online table of contents at http://ajcn.nutrition.org.…”
Section: Introductionmentioning
confidence: 99%
“…In a retrospective cohort study, excessive maternal GWG had an adverse impact on the risk of childhood overweight and abdominal adiposity (Ensenauer et al 2013). Kaar et al further reported that maternal prepregnancy BMI was not only associated with increased general adiposity (BMI) and abdominal adiposity (waist circumference) in offspring but visceral adipose tissue at age 10 years (Kaar et al 2014). A recent study points to an association between maternal excess weight in pregnancy and offspring BMI increase from adolescence to adulthood (Lawrence et al 2014).…”
Section: Maternal Prepregnancy Obesity and Gestational Weight Gainmentioning
confidence: 99%
“…Early pregnancy obesity has also been associated with an increased risk of premature death in adult offspring (Reynolds et al 2013a). To further the negative impact, maternal prepregnancy BMI was also associated with increased offspring insulin resistance at age 10 years (Kaar et al 2014) and an increased risk of developing T2DM (Dabelea et al 2008). …”
Section: Maternal Prepregnancy Obesity and Gestational Weight Gainmentioning
confidence: 99%
“…Указывается, что своевременная коррекция диеты беременной и кормящей женщины способствует профи-лактике детского ожирения [33,38].…”
Section: жировой обменunclassified